Eating habits of children and adolescents during the COVID-19 era: A systematic review - Pourghazi, Farzad; Eslami, Maysa; Ehsani, Amir; Ejtahed, Hanieh-Sadat; Qorbani, Mostafa (Frontiers in Nutrition, 2022)
The COVID19 pandemic has affected all aspects of people's lives. Eating habit plays a crucial role in children and adolescents’ physical and mental development and the impacts might last until adulthood. This systematic review aimed to summarize a comprehensive and updated overview of eating habits changes due to COVID19 confinements among children and adolescents. A systematic literature search was performed in three databases for all the English studies published from the start of the confinements until April 2022. Two researchers screened articles independently and included observational studies which evaluated children's and adolescents' eating habits before and during confinements. The quality of the included studies was assessed by Newcastle-Ottawa Quality Assessment checklists for cross-sectional and cohort studies. Among 2436 studies, 39 final full-text articles were included. The total participants of this systematic review consist of 159,391 children and adolescents. Seven categories were identified: daily eating patterns, junk food, beverage, fruits and vegetables, milk and dairy, protein-rich foods, and legumes and cereals. In summary, most of the included studies reported a significant increase in consumption of home-cooked meals, amount of food, snack, french fries, sweets, fruits, vegetables, legumes, bread, and bakery products. On the other hand, studies demonstrated significantly lower intake of fast food and soft drink. The studies reported controversial results about breakfast consumption, sugar-added drinks, caffeinated drinks, milk and dairy products, protein-rich foods (including meat, fish, egg and chicken, and poultry), rice, and cereal. Changes in children's and adolescents' eating habits during the COVID-19 era were both positive and negative, for example, a decrease in fast food, fruit, and vegetable consumption versus an increase in snacking and sweet consumption. Both changes have significant short-term and long-term impacts on population health. This study could provide us with insight into the changes in eating habits in children and adolescents in the COVID-19 era, which we can use to limit the negative consequences on health.